Shaping Communicative Identity Through Group- Discovery Learning Model: Enhancing 21st Century Skills in Language Education - Helda, Trisna; Indriyani, Vivi; Yusandra, Titiek Fujita; Marni, Silvia; Yulianti DN, Upit (Universitas PGRI Sumatera Barat, 2025)
This study investigates the impact of the Group-Discovery Learning Model on students’ communicative identity and the development of essential 21st-century skills, including critical thinking, creativity, collaboration, and communication. This model is rooted in constructivist principles and encourages active learning through peer interaction, problem-solving tasks, and self-directed inquiry. Employing a quasi-experimental design, data were collected from 104 high school students across two schools in Padang who participated in either experimental or control classes. A validated performance-based assessment instrument was used to measure student outcomes across multiple dimensions of skill development. The results revealed significant improvements in 21st-century skills among students in the experimental group, with average post-treatment scores of 84.3 and 84.8, indicating a positive effect of the model. The normalized gain (N-Gain) scores showed medium effects (0.51 and 0.45), demonstrating measurable progress over four sessions. No significant interaction was found between the school category and the model's effectiveness, suggesting its potential adaptability across diverse educational settings. These findings support the Group-Discovery Learning Model as an effective approach for enhancing both cognitive and social competencies essential for modern learners. Despite these positive outcomes, challenges remain, particularly in developing higher-order critical thinking skills such as evaluating peer arguments and synthesizing complex ideas. This suggests that while the model fosters collaborative learning and engagement, additional scaffolding may be required to strengthen analytical reasoning. The study recommends integrating digital tools into the model to enrich collaborative learning experiences and reinforce students’ evolving communicative identities in contemporary language education.